1970
DOI: 10.1042/bj1180143
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism in mouse pancreatic islets

Abstract: 1. Rates of glucose oxidation, lactate output and the intracellular concentration of glucose 6-phosphate were measured in mouse pancreatic islets incubated in vitro. 2. Glucose oxidation rate, measured as the formation of (14)CO(2) from [U-(14)C]glucose, was markedly dependent on extracellular glucose concentration. It was especially sensitive to glucose concentrations between 1 and 2mg/ml. Glucose oxidation was inhibited by mannoheptulose and glucosamine but not by phlorrhizin, 2-deoxyglucose or N-acetylgluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
154
2
1

Year Published

1975
1975
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(174 citation statements)
references
References 26 publications
17
154
2
1
Order By: Relevance
“…Similarly, the majority of reports suggest that sulphonylureas do not significantly affect the oxidation of 14 C-glucose or the generation of acidic glucose metabolites [30,31,32], at least in long-term incubations. However, an earlier study indicated that tolbutamide increased the oxidation of U-[ 14 C] glucose by 33% and doubled the output of lactate in mouse islets [33]. These findings are essentially consistent with our present findings that tolbutamide caused a 64% increase in the generation of acidic metabolites from glucose.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, the majority of reports suggest that sulphonylureas do not significantly affect the oxidation of 14 C-glucose or the generation of acidic glucose metabolites [30,31,32], at least in long-term incubations. However, an earlier study indicated that tolbutamide increased the oxidation of U-[ 14 C] glucose by 33% and doubled the output of lactate in mouse islets [33]. These findings are essentially consistent with our present findings that tolbutamide caused a 64% increase in the generation of acidic metabolites from glucose.…”
Section: Discussionsupporting
confidence: 83%
“…Such studies may also help to explain the puzzling observation that mannoheptulose was a more effective inhibitor of glycolytic flux in oxygenated as compared with anoxic islets. An unexpected behaviour of mannoheptulose is not without precedent, since Ashcroft et al [19] found that the compound markedly inhibited glucose oxidation and yet was without effect on the production of lactate in isolated mouse islets.…”
Section: Discussionmentioning
confidence: 99%
“…The 14CO2 was absorbed in hyamine and counted by liquid scintillation spectrometry as described by Ashcroft et al [13]. For measurements of islet content of cyclic AMP, batches of 20islets were first incubated in 10gl bicarbonate-medium containing 2mmol/l of glucose for 10min at 37 ~ and then incubated for a further 2.5 min following addition of 5 lxl medium containing glucose 2 or 50mmol/1.…”
Section: Methodsmentioning
confidence: 99%